A Carbon‐Neutral Photosynthetic Microbial Fuel Cell Powered byMicrocystis aeruginosa. (1st July 2015) - Ma, Meirong; Cao, Limin; Chen, Li; Ying, Xiaofang; Deng, Zongwu
ABSTRACT: : A photosynthetic microbial fuel cell (m‐PMFC) is developed for generating electricity by harnessing solar energy using Microcystis aeruginosa . In this m‐PMFC, commensal bacteria can consume the nutrients that Microcystis aeruginosa produces to generate electricity so that no net CO2 production occurs. A b‐MFC is constructed to confirm the role of commensal bacteria in electric generation. An s‐PMFC is constructed to confirm the contribution of Microcystis aeruginosa as substrates. The power outputs of m‐PMFCs exhibit no significant difference in terms of different inoculation amount of Microcystis aeruginosa or light/dark cycles. The power density of m‐PMFC exhibits similar response to bubbling of N2 and O2 as that of b‐MFC, as confirmed by cyclic voltammetry analysis of m‐PMFC and b‐MFC. Scanning electron microscope images demonstrate that the biofilm of m‐PMFC consists mainly of commensal bacteria. These results suggest that commensal bacteria act as the main biocatalysts and Microcystis aeruginosa as the anode substrates in the m‐PMFC.